External Audit of Public Finance in Function of Macroeconomic Stability - Snežana Ljubisavljević; Milka Grbić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The generally accepted view is that to achieve macroeconomic stability and sustainable economic growth, good management of public finance is necessary. The concept of external audit of public finance, as a subject of research in this paper, is analyzed as an integral element of public financial management system, which significantly determines transparent, responsible, and stable functioning of the public sector in any economy. In accordance with the subject, the goal of the research is to emphasize the importance of external audit of the execution of budget at all levels of government in the process of achieving and maintaining macroeconomic stability, with a special focus on the Republic of Serbia. Recognizing the complexity of this subject matter, qualitative methodology is applied, based on the dominant application of method of analytical description. The paper concludes that external audit of public finance has potential effects on the reduction of budget deficit and public debt. Given that ministries and other state administration bodies know that their financial reports can be audited at any time, external audit has a preventive effect in terms of awareness-raising for greater responsibility with managing public funds. Furthermore, recommendations of the State Audit Institution, to the extent that they are implemented, contribute to saving and efficient use of resources in certain areas.
Keywords: M42; E60; H60; 330; external audit; State Audit Institution; public finance; budget deficit; public debt; economy